Creating Acoustic Maps Employing Supercomputing Cluster - CZYŻEWSKI, Andrzej; KOTUS, Józef; SZCZODRAK, Maciej (Archives of Acoustics, 2011)
The implemented online urban noise pollution monitoring system is presentedwith regard to its conceptual assumptions and technical realization. A concept ofthe noise source parameters dynamic assessment is introduced. The idea of noisemodeling, based on noise emission characteristics and emission simulations, was developedand practically utilized in the system. Furthermore, the working systemarchitecture and the data acquisition scheme are described. The method for increasingthe speed of noise map calculation employing a supercomputer is explained. Thepractical implementation of noise maps generation and visualization system is presented,together with introduced improvements in the domain of continuous noisemonitoring and acoustic maps creation. Some results of tests performed using thesystem prototype are shown. The main focus is put on assessing the efficiency of theacoustic maps created with the discussed system, in comparison to results obtainedwith traditional methods.